Lignocellulosic Bio Fuel Production In Iceland, A System Dynamics Approach. - Emil Þorvaldsson 1989- (2017)
Iceland is an island with a lot of energy potential in the form of hydro- and geother- mal energy. But still there is enormous amount of fossil fuel imports each year. This posses an enormous economic problem for Iceland as fossil fuels are non renewable and will eventually run out. The paper explores the possibility of utilizing Wood grown in Iceland through the process of pyrolysis and upgrading of the pyrolysis products with current known technology and product yields. A literary review conducted on the topic focusing on the production of fuels, showed that 400 t / d facility utilizing a fluidizing bed reactor, where the pyrolysis products would then be upgraded into fuels through further processing. Expanding on a forestry model proposed by Sverdrup and Ólafsdóttir (2017) and assuming that all grassland in Iceland is rigth for forestry, We conclude that maxi- mum utilization of a 400 t / d would at the earliest be in the year 2050, if all of the wood harvested in Iceland would go through the process. The latest would be in the year 2063 if 30 % of all harvested wood would be utilized. Maximum yields amount to 49 thousand metric tons of fuel. This amounts to around 10% of the current total fossil fuel use in Iceland. These results are promissing, as they show that it is indeed possible to produce fuel for native wood in Iceland. but further reasearch is needed as to what other possible sources could be utilized to satisfy fuel demand. Á Íslandi eru miklir möguleikar er kemur að endurnýjanlegri orku. Áræðni á óendurný- janlega orkugjafa valda þó miklum efnahagslegum erfiðleikum fyrir ísland, þar sem upp- spretta þeirra mun á endanum klárast. Þessi ritgerð skoðar möguleikan á nýtingu íslensk viðar til framleiðslu á lífeldsneyti með núverandi tækni og afköstum. Ritrýni leiddi í ljós að möguleikar eru á framleiðslu uppá 400 t / d . Niðurstaða útreikninga með hliðsjónar af skógræktarmódeli sem lýst var af Sverdrup and Ólafsdóttir (2017) með þeirri viðbót að gert er ráð fyrir að allt graslendi á íslandi er ...